Viewing the ‘invisible women’: A qualitative study on the empowerment effect of Chinese rural women in the context of short video platforms - Le Cao (Acta Psychologica)
As a medium of empowerment, short video platforms have significantly increased the social visibility of rural women in China, transforming them from “invisible women” in mainstream society to “visible women” in the virtual space. This study adopts a feminist qualitative approach, conducting in-depth interviews with 17 rural female users of the Kuai platform and analysing their experiences through a three-tiered coding framework (open, axial, and selective) using Nvivo11. Our findings reveal two dimensions of empowerment: internal empowerment (characterized by self-determined content creation [“visible initiative”] and negotiated identity performance [“constrained subjectivity”]) and external empowerment (manifested as algorithm-driven social connections [“instrumental sociality”]). Crucially, we propose the concept of superficial (surface-level) empowerment-a form of digital agency that appears transformative but remains contingent on patriarchal platform logic. While these women gain economic benefits and temporary recognition through live commerce and persona curation, their autonomy is illusory, constrained by algorithmic biases reinforcing traditional gender roles (e.g., “virtuous mother” stereotypes) and survival-driven compromises with audience expectations. This study challenges the techno-optimist narrative of digital empowerment by demonstrating how rural women's “visibility” on short video platforms mirrors, rather than disrupts, existing power hierarchies.